2022
DOI: 10.3389/fmed.2022.877220
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width Is Associated With Adverse Kidney Outcomes in Patients With Chronic Kidney Disease

Abstract: BackgroundChronic kidney disease (CKD) is a global public health issue. Red blood cell distribution width (RDW) is a recently recognized potential inflammatory marker, which mirrors the variability in erythrocyte volume. Studies indicate that elevated RDW is associated with increased risk of mortality in CKD patients, while evidence regarding the impact of RDW on kidney outcome is limited.MethodsAltogether 523 patients with CKD stage 1–4 from a single center were enrolled. We identified the cutoff point for RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(45 reference statements)
0
4
1
Order By: Relevance
“…Pusuroglu et al reported a negative correlation between the RDW and eGFR in hypertensive patients, [ 22 ] and similar findings were observed in chronic kidney disease. [ 33 ] However, in the present study, we did not find a significant correlation between anisocytosis and the eGFR.…”
Section: Discussioncontrasting
confidence: 91%
“…Pusuroglu et al reported a negative correlation between the RDW and eGFR in hypertensive patients, [ 22 ] and similar findings were observed in chronic kidney disease. [ 33 ] However, in the present study, we did not find a significant correlation between anisocytosis and the eGFR.…”
Section: Discussioncontrasting
confidence: 91%
“…Increased RDW has been reported to be an emerging biomarker of abnormal red blood cell metabolism and survival, potentially representing oxidative stress, inflammation, and various diseases; thus, an increased RDW may be considered an indicator of inflammation [ 47 ]. Additionally, abnormally increased RDW has been identified as a negative prognostic factor in patients with advanced heart failure who have recently experienced decompensation, independent of the presence of anemia or malnutrition, that offers superior performance compared with more traditionally used indicators [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…RDW‐SD is calculated from the diameter‐of‐erythrocyte distribution curve at 20% above baseline and is expressed in femtolitres [ 22 , 23 , 24 ]. Originally, RDW was used to evaluate anisocytosis of red blood cells and to differentiate causes of anemia [ 25 , 26 , 27 , 28 , 29 ]. Recently, however, RDW has been employed in various clinical fields.…”
Section: Discussionmentioning
confidence: 99%